Vaccination - Milicic, Anita (Henry Stewart Talks, 2021)
The history of vaccination, Mechanisms of vaccine action, Types of vaccine, Vaccine development process, Vaccine platforms, Vaccine adjuvants, Pre-clinical and clinical testing of vaccine candidates